Archaeology, Metal Detecting, and Citizen Science in the Czech Republic. Issue 3 (August 2022) - Komoróczy, Balázs
Abstract: Although the legal conditions are perceived as restrictive, metal detecting has become a popular activity in the Czech Republic. In 2017, a questionnaire survey revealed that a significant segment of this community is made up of passionate people interested in history and archaeology. The majority of professional archaeologists consider metal-detecting finds to be important and believe that cooperation with metal detectorists is necessary, beneficial, and acceptable. A collaborative project called "Joint Forces in Order to Discover the Common Archaeological Heritage of the South Moravian Region" aims to create conditions for citizen science among the metal detectorists in the region. By using tools such as expert workshops for the employees of professional institutions, meetings, educational workshops and field activities with interested members of the public, and production and distribution of printed and digital information materials, the partners in the program have long endeavored to improve the mutual understanding of all relevant actors of society and administration. The creation of circles of citizen collaborators is in progress in several archaeological institutions; nevertheless, this process is far from over. In 2020, with the creation of the Portal of Amateur Collaborators, this activity acquired a unified digital scheme for the registration of finds.